Book review: Kelly, Anthony and Westoby, Peter. 2018: Participatory Development Practice: Using Traditional and Contemporary Frameworks. (April 2020) - Cochrane, Logan
Kelly, Anthony and Westoby, Peter. 2018: Participatory Development Practice: Using Traditional and Contemporary Frameworks . London, UK: Practical Action Publishing. 234 pp. £23.70 (Paperback). ISBN: 9781853299992.